2017
DOI: 10.1021/acsomega.7b00522
|View full text |Cite
|
Sign up to set email alerts
|

Envisaging the Structural Elevation in the Early Event of Oligomerization of Disordered Amyloid β Peptide

Abstract: In Alzheimer’s disease (AD), amyloid β (Aβ) protein plays a detrimental role in neuronal injury and death. Recent in vitro and in vivo studies suggest that soluble oligomers of the Aβ peptide are neurotoxic. Structural properties of the oligomeric assembly, however, are largely unknown. Our present investigation established that the 40-residue-long Aβ peptide (Aβ40) became more helical, ordered, and compact in the oligomeric state, and both the helical and β-sheet components were found to increase significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 95 publications
2
26
0
Order By: Relevance
“… 18 The amide III region (1230–1300 cm –1 ) was also enriched with predominant α-helical marker bands ( Figure 2 A and Table 2 ). 18 , 36 38 It was composed of a major shoulder band at 1262 cm –1 that marked the signature of pure helix. 36 , 38 The signature of the extended helix/2.5 1 -helix conformation similar to poly- l -glutamic acid conformation was embarked at 1268 and 1277 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 The amide III region (1230–1300 cm –1 ) was also enriched with predominant α-helical marker bands ( Figure 2 A and Table 2 ). 18 , 36 38 It was composed of a major shoulder band at 1262 cm –1 that marked the signature of pure helix. 36 , 38 The signature of the extended helix/2.5 1 -helix conformation similar to poly- l -glutamic acid conformation was embarked at 1268 and 1277 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…The Raman band patterns and curve-fitting analysis to amide I band often provide ample information related to protein backbone conformation and its stability. 18 , 36 , 37 , 43 46 Dong et al and others performed initial Raman investigation on dimeric and hexameric insulin aggregates, measuring amide I band behavior in different sample conditions. 34 , 47 Our laboratory also derived the structural content of amyloid aggregates of Aβ peptides using the amide I curve-fitting protocol, as suggested by Dong et al and Maiti et al 34 , 37 In our current investigation, curve fitting to the Raman amide I showed that ∼54% of residues in insulin monomer preferred α-helical secondary structure and the component band was at 1658 cm –1 ( Figure 2 B and Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because SFG signals rely on a tensor product of the IR transition dipole moment and the Raman polarizability tensor, the amide II SFG signals are too weak to be detected in the disordered, α-helical structure and β-hairpin-like structure. Indeed, with the exception of one example of an amide II signal reported in an intermolecular β-sheet structure by Yan et al, the amide II SFG spectra have not been applied to address the issue of amyloid formation when the SFG technique was applied to investigate the interfacial proteins. , However, some recent studies have shown that upon formation of multistranded β-sheet structures, long-range vibrational coupling from intermolecular β-sheet contacts can largely enhance the amide II signals and make the amide II Raman spectra become visible; see Table S1. For example, the amide II Raman signals are absent in the disordered α-synuclein and appear when α-synuclein starts to aggregate to form oligomeric β-sheet structures. , It can be naturally anticipated that amide II SFG signals are active in β-sheet oligomers and fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…9,14,23,27,33,47,57,58 A partial unfolding of the monomeric globular protein produces a molten globule like structure that is comparable to the amyloidogenic protein intermediates, acting as the nucleating form. 29,50,55,[59][60][61] In the absence of zinc at physiological pH, HI is primarily present as a conformationally stable dimer;…”
Section: Discussionmentioning
confidence: 99%